Annular pancreas: A rare cause of duodenal obstruction - Sylla, Moussa; Ossibi, Pierlesky Elion; Soumana, İsmaël Dandakoye and Tenkorang, Somuah and Ibn Majdoub, Karim and Toughrai, İmane and Mazaz, Khalid (Journal of Surgery and Medicine, 2019)
Annular pancreas is a rare congenital anomaly. It occurs in 1 in 20,000 of the population. Annular pancreas clinically manifests as digestive stenosis which may be complicated with peptic ulcer. Digestive derivation surgery remains the essential treatment for annular pancreas. We report the case of an 18-year-old female patient with duodenal stenosis caused by an annular pancreas.